Essential Surgery / Problems, Diagnosis and Management: Fifth Edition - Harper Simon J. F; Quick Clive R. G; Reed Joanna B; Saeb-Parsy Kourosh (Churchill Livingstone - Elsevier, 2014)
The main aim of this book is to stimulate the reader to a greater enjoyment and understanding of the practice of surgery. Principles of Surgical Care, Disease Processes, Diagnostic Techniques, Perioperative Care, Principles of Accident Surgery, Symptoms and Diagnosis and Management, Abdomen and General Principles, Upper Gastrointestinal and Hepatobiliary, Coloproctology, Thoracic Surgery Excluding Cardiac, Groin and Male Genitalia, Urology, Cardiovascular Disorders, Disorders of the Breast and Skin, Disorders of the Head and Neck, Neonatal and Pediatric Surgery, Index.